2021
DOI: 10.18632/aging.203482
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cerebrovascular abnormalities in the pathogenesis and progression of Alzheimer’s disease: an adrenergic approach

Abstract: Alzheimer’s disease (AD), as the most common neurodegenerative disease in elder population, is pathologically characterized by β-amyloid (Aβ) plaques, neurofibrillary tangles composed of highly-phosphorylated tau protein and consequently progressive neurodegeneration. However, both Aβ and tau fails to cover the whole pathological process of AD, and most of the Aβ- or tau-based therapeutic strategies are all failed. Increasing lines of evidence from both clinical and preclinical studies have indicated that age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…Although higher CVR in the AD signature regions that typically thin or atrophy throughout AD progression is associated with lower MCI risk, 24–26 regional volumes other than the hippocampus were not associated with MCI risk, indicating that CVR changes may precede morphometric changes, consistent with other studies suggesting BBB breakdown and CBF dysregulation precede neurodegeneration 39,40 . These findings corroborate cross‐sectional human studies and rodent models, which correlate CVR reduction with AD progression 6–10,12–16,22,23 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although higher CVR in the AD signature regions that typically thin or atrophy throughout AD progression is associated with lower MCI risk, 24–26 regional volumes other than the hippocampus were not associated with MCI risk, indicating that CVR changes may precede morphometric changes, consistent with other studies suggesting BBB breakdown and CBF dysregulation precede neurodegeneration 39,40 . These findings corroborate cross‐sectional human studies and rodent models, which correlate CVR reduction with AD progression 6–10,12–16,22,23 …”
Section: Discussionsupporting
confidence: 85%
“…39,40 These findings corroborate cross-sectional human studies and rodent models, which correlate CVR reduction with AD progression. [6][7][8][9][10][12][13][14][15][16]22,23 Human studies have shown that participants with MCI and dementia have lower CVR compared to cognitively unimpaired individuals. 23 among a cohort of younger subjects, indicating that CVR-related changes in cognition may be independent from the progression of AD-related pathologies.…”
Section: Without Adjustment For Plasma Biomarkersmentioning
confidence: 99%
“…Recent studies have shown that atherosclerosis ( Lin et al, 2022 ), cerebrovascular endothelial damage ( Xi et al, 2012 ), the Aβ clearance dysfunction ( Xi et al, 2013 ), the oxidative damage resulting in the blood–brain barrier (BBB) broken, and cerebral microvascular pathology ( Boese et al, 2020 ; Kurz et al, 2021 ; Owens et al, 2022 ) have a close relationship with the advancement of AD. These findings suggest that cerebrovascular dysfunction might be key pathogenesis in the development of AD ( Li et al, 2021 ). It is reported that oxidative damage is an important case in the progress of cerebrovascular pathology ( Chen et al, 2022 ; Martini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 93%
“…This decreased expression could contribute to an impaired efflux of neurotoxic substances and Aβ peptides, potentially exacerbating AD pathology [113]. Moreover, recent studies indicate that certain MRPs may be involved in clearing Aβ peptides from the brain, with the dysregulated MRP function potentially contributing to Aβ accumulation and neurotoxicity [15], given the potential connection between the MRP dysfunction and AD pathology.…”
Section: Multidrug Resistance-associated Proteins (Mrps)mentioning
confidence: 99%
“…In line with this, the two-hit vascular hypothesis of AD suggests cerebrovascular damage (hit 1) as an initial insult that is self-sufficient to initiate neuronal injury and neurodegeneration. Additionally, it promotes the buildup of Alzheimer's Aβ toxin in the brain (hit 2) [15].…”
Section: Introductionmentioning
confidence: 99%